The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s40571-021-00434-w
|View full text |Cite
|
Sign up to set email alerts
|

A statistical DEM approach for modelling heterogeneous brittle materials

Abstract: By utilizing numerical models and simulation, insights about the fracture process of brittle heterogeneous materials can be gained without the need for expensive, difficult, or even impossible, experiments. Brittle and heterogeneous materials like rocks usually exhibit a large spread of experimental data and there is a need for a stochastic model that can mimic this behaviour. In this work, a new numerical approach, based on the Bonded Discrete Element Method, for modelling of heterogeneous brittle materials i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…These steps are taken at each iteration to obtain the stress tensor σ and the corresponding consistent tangent C ep to be used in equation (30).…”
Section: Elasto-viscoplastic Evolution Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…These steps are taken at each iteration to obtain the stress tensor σ and the corresponding consistent tangent C ep to be used in equation (30).…”
Section: Elasto-viscoplastic Evolution Problemmentioning
confidence: 99%
“…Numerical approaches in fracture mechanics can be broadly classified into two categories: discrete and continuum methods [25]. Discrete approaches, such as the Flat-Joint Method (FJM), Discrete Element Method (DEM), non-ordinary state-based peridynamics, and Discontinuous Deformation Analysis (DDA), have been used by researchers [1,4,[26][27][28][29][30][31] to model the fracture in a Brazilian splitting test. These methods provide an insight into the (quasi-)brittle fracture behavior of the material.…”
mentioning
confidence: 99%
“…Hence, a so-called rectangular sensing region (RSR) was defined, large enough to avoid local effects, such as voids and microcracks or singular grains, but small enough to capture the nearly constant indirect tensile strain region close to the centre of the disc. Furthermore, it is crucial that the region covers the point of crack initiation, which does not always coincide with the centre of the disc [3,15]. To this end, five tests of each rock were conducted with the high-speed camera set to 381,000 fps in order to capture the full surface of the disc, see Figure 5.…”
Section: Dynamic Brazilian Disc Testmentioning
confidence: 99%
“…By utilizing numerical simulations, insights can be gained regarding the hard rock drilling process that otherwise would be difficult to obtain. A recently developed statistical model by Wessling et al [3], based on the discrete element method, has been shown to capture typical rock fracture behaviour. However, in order for this model to be accurate, precise information regarding the dynamic properties of the rock material is crucial.…”
Section: Introductionmentioning
confidence: 99%